2005
DOI: 10.1534/genetics.104.035030
|View full text |Cite
|
Sign up to set email alerts
|

Africanization in the United States

Abstract: The expansion of Africanized honeybees from South America to the southwestern United States in Ͻ50 years is considered one of the most spectacular biological invasions yet documented. In the American tropics, it has been shown that during their expansion Africanized honeybees have low levels of introgressed alleles from resident European populations. In the United States, it has been speculated, but not shown, that Africanized honeybees would hybridize extensively with European honeybees. Here we report a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 79 publications
5
56
1
Order By: Relevance
“…This finding is in agreement with results in tropical and subtropical regions elsewhere (Clarke et al 2002;Pinto et al 2005;Whitfield et al 2006). A numerical asymmetry between Africanized and European honey bees can explain these results (Rinderer et al 1991).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in agreement with results in tropical and subtropical regions elsewhere (Clarke et al 2002;Pinto et al 2005;Whitfield et al 2006). A numerical asymmetry between Africanized and European honey bees can explain these results (Rinderer et al 1991).…”
Section: Discussionsupporting
confidence: 92%
“…The numerical superiority of African drones in congregation areas where queens mate mainly arises from proportionately greater male production by Africanized colonies ) and Africanized drones' parasitism of European colonies, which also suppress the production of European drones (Rinderer et al 1985). In combination, these factors favor the introgression of African paternal alleles into European colonies while resulting in the eventual displacement of European nuclear markers (Rinderer et al 1991;Pinto et al 2005;Whitfield et al 2006). However, in temperate zones, feral populations with African ancestry may not reach the high densities observed in tropical areas, giving their European counterparts better opportunities to compete reproductively (Sheppard et al 1991;QuezadaEuán 2007) as our findings suggest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done to investigate the patterns of hybridization between bees of European and African descent occurring in this population of feral honey bees since the late 1990s (Baum 2003;2005;Pinto 2004;Pinto 2005). In 2013, 5.60 km 2 of the original WWR study area was resurveyed, and 89 of the original 109 trees that had been identified earlier were re-visited and sampled for honey bees if a colony was present.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…The relative importance of the population size of resident European honey bees plus the environmental and beekeeping characteristics in different localities on the process of Africanization is controversial (Smith et al, 1989;Rinderer et al, 1991;Sheppard et al, 1991). One of the main problems in elucidating the relative importance of different factors and the mechanisms involved in the process is the lack of long term detailed studies before, during and after the arrival of colonizing swarms (QuezadaEuán, 2000; Pinto et al, 2005). The study of the expansion and establishment of AHBs in NW Mexico can provide additional information to test hypothesis regarding the relative effect of the size of the resident EHB population and that of climatic and geographic barriers (Quezada-Euán et al, 2003) different from the ones that AHBs have encountered during their expansion history across tropical and subtropical Mexico.…”
Section: Introductionmentioning
confidence: 99%